Resources for Structural Optimization of Gas-hydrodynamic Measuring Transducers - Yevhen Pistun; Halyna Matiko; Hanna Krykh (Energy Engineering and Control Systems)
The paper presents the analysis of the resources of structural and parametric optimization of gas-hydrodynamic measuring transducers of physical and mechanical parameters of fluids. Resources such as the number of throttles and their arrangement in the diagram, type of throttle elements, measuring channels with a certain type of output signal, the supply mode of the measuring transducer can be integrated into the design process of the measuring transducer of a specific parameter. A mathematical apparatus based on set theory and combinatorial analysis is proposed for synthesizing the possible structures of throttle diagrams, graph theory – for forming a set of measuring channels. The authors have given examples demonstrating the possibilities of building different diagrams of measuring transducers using the resources for structural synthesis. The proposed resources are the means of structural and parametric optimization for synthesizing the gas-hydrodynamic measuring transducers with optimal characteristics.